Intergenerational redistribution in a pay-as-you-go pension system - Jacob Lundberg (Research Institute of Industrial Economics (IFN), 2024)
This study provides a comprehensive analysis of the generational wealth transfer within Sweden's public pay-as-you-go pension system introduced in 1960. Using extensive administrative registers, the paper quantifies the contributions made and benefits received by each birth cohort. The findings reveal a substantial fiscal imbalance favouring the initial generation (born in the early 20th century), who received a net gain of 1.5 trillion in today's present value, equivalent to up to 13% of their discounted lifetime income. This windfall for the initial generation resulted in an implicit tax on current workers, accounting for 70% of their pension contributions. However, the study also highlights the effectiveness of Sweden's 1999 notional defined-contribution pension reform in stabilizing this imbalance. Unlike many international counterparts, Sweden's reformed system successfully mitigates further generational inequities in the pension system.
Keywords: H55; N34; 330; Pensions; social security; pay-as-you-go; generational equity; generational accounting